Donner la parole : à quel prix ? - Mathilde Zbaeren (Contextes)
This article proposes to question the success of the notion of restitution in literature studies in order to consider the effects of an imaginary of literature as a "gift". Through the prism of the case provided by Jean Hatzfeld's collection of testimonies in Rwanda, the aim is to measure the effects of the importation into literary studies of the notions of "restitution", "exchange of gifts" and "countergift", inherited from the works of Marcel Mauss and Pierre Bourdieu. Based on the idea that non-fictional literature forms are linked to deontological and political demands for the restoration of debt, this article argues that collections of voices require the overcoming of the assimilation of literature to the universal, in order to emphasize its commitments and effects within the chain of exchange that constitutes the social bond. The distinction between literary and ethnographic restitution, thus made obsolete by non-fictional forms, requires documentary literature and field writing to think of restitution in its material dimension, by virtue of the "participation" in the field of the potential readers of these productions.